PENGEMBANGAN MONEKA (MONOPOLI EKSPONEN AREA) SEBAGAI MEDIA PEMBELAJARAN BERBASIS PERMAINAN UNTUK MENUMBUHKAN KEMAMPUAN PEMAHAMAN KONSEP - Kholishoh, Millah; Rini Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The survey shows that students’ conceptual understanding of exponent material is still low. This is proven by 55% of students stating that a tool is needed to help understand material that has many formulas such as exponents. This study aims to develop learning media in the form of game-based mathematical monopoly to help students develop their ability to understand the concept of exponent material for class X. This study uses the RnD method with the ADDIE model which includes (analysis, design, development, implementation, evaluation). The data collected for the purposes of this research were obtained through media needs questionnaires, observations, and interviews. The media developed has gone through validation by material experts with an average of 3,7 in the very valid category and validation by media experts with an average of 3,7 in very valid category. Then media was tested on students and an average score of 3,1 was obtained in the good category. The result of this study are contextual monopoly media that have been modified according to the objectives of learning mathematics for class X exponent material that is valid and practical so that it can foster students’ conceptual understanding abilities.